HAMBATAN YANG DIHADAPI GURU DALAM MENERAPKAN STRATEGI PEMBELAJARAN BERBASIS PROYEK PADA PEMBELAJARAN PKN - Muhammad Mona Adha; Muhammad Kaulan Karima; Amanda Kurnia Pangestu; Feristina Yuliani; Figta Nuril Huda; Hikmatul Aini (LPPM Universitas Cipta Mandiri, 2026)
This study aims to identify and analyze the obstacles faced by teachers in implementing project-based learning (PjBL) strategies in Civics subjects at SD Negeri 1 Serdang Lampung Selatan Bandar Lampung. This study used a descriptive qualitative approach. Data were collected through field observations, in-depth interviews with Civics teachers, and surveys (questionnaires) to map teachers' perceptions of existing obstacles. The results of the study indicate that the main obstacles faced by teachers at SD Negeri 1 Serdang Lampung Selatan Bandar Lampung include: (1) Limited time allocation that is not commensurate with the complex PjBL syntax; (2) Lack of resources and supporting facilities for project learning; (3) Teachers' difficulties in designing projects that are contextual and relevant to Civics material; and (4) Challenges in managing student group dynamics, such as boredom and lack of active participation. This study concludes that although PjBL is recognized as important, support in the form of intensive training for teachers and more flexible curriculum adjustments are needed to overcome these obstacles.